Masculinity Meets Postmodernism: Theorizing the 'Man-Made’ Man - Frank, Blye (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1997)
Contemporary postmodern philosophers are upsetting the knowledge applecart by challenging the underpinnings of modem thought on a variety of fronts. Aerial views, those grand narratives (Lyotard, 1984) based on foundational ‘truths’ that do not exist in quite the way in which we have often assumed, provide for the consumption of a world located within and based upon notions of epistemological essentialism. Dichotomous underpinnings of individualism and structuralism continue to permeate and saturate representations of men’s lives, attempting to collapse and control the messiness as binary, while, at the same time, masking recycled theories of biological and social determinism. In the absence of “situated knowledge” (Haraway, 1988) arising within local narratives, we have received a “man-made” theory-world of men that offers up a fixity; linear, bounded, dichotomized and disconnected. This paper grapples with some of Frank’s ideas about the relationship between the investigation of men’s lives and the resulting created knowledge which has helped shape our understandings of ourselves as men, our relation to others and the environment we inhabit daily.